Publisher Correction: Fe-functionalized paramagnetic sporopollenin from pollen grains: one-pot synthesis using ionic liquids - C. Chiappe (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.